Identification of novel long non-coding RNAs in triple-negative breast cancer - Shen, Xiaokun (Oncotarget, 2015)
Triple-negative breast carcinomas (TNBC) are characterized by particularly poor outcomes, and there are no established markers significantly associated with prognosis. Long non-coding RNAs (lncRNAs) are subclass of noncoding RNAs that have been recently shown to play critical roles in cancer biology. However, little is known about their mechanistic role in TNBC pathogenesis. In this report, we investigated the expression patterns of lncRNAs from TNBC tissues and matched normal tissues with Agilent Human lncRNA array. We identified 1,758 lncRNAs and 1,254 mRNAs that were differentially expressed (≥ 2-fold change), indicating that many lncRNAs are significantly upregulated or downregulated in TNBC. Among these, XR_250621.1 and NONHSAT125629 were the most upregulated and downregulated lncRNAs respectively. qRT-PCR was employed to validate the microarray analysis findings, and results were consistent with the data from the microarrays. GO and KEGG pathway analysis were applied to explore the potential lncRNAs functions, some pathways including microtubule motor activity and DNA replication were identified in TNBC pathogenesis. Our study revealed that a set of lncRNAs were differentially expressed in TNBC tissues, suggesting that they may play role in TNBC. These results shed light on lncRNAs’ biological functions and provide useful information for exploring potential therapeutic targets for breast cancer.